Microfinance Meets the Market - Cull, Robert (2012)
In this paper, we examine the economic logic behind microfinance institutions and consider the movement from socially oriented nonprofit microfinance institutions to for-profit microfinance. Drawing on a large dataset that includes most of the world's leading microfinance institutions, we explore eight questions about the microfinance "industry": Who are the lenders? How widespread is profitability? Are loans in fact repaid at the high rates advertised? Who are the customers? Why are interest rates so high? Are profits high enough to attract profit-maximizing investors? How important are subsidies? The evidence suggests that investors seeking pure profits would have little interest in most of the institutions we see that are now serving poorer customers. We will suggest that the future of microfinance is unlikely to follow a single path. The recent clash between supporters of profit-driven Banco Compartamos and of the Grameen Bank with its "social business" model offers us a false choice. Commercial investment is necessary to fund the continued expansion of microfinance, but institutions with strong social missions, many taking advantage of subsidies, remain best placed to reach and serve the poorest customers, and some are doing so at a massive scale. The market is a powerful force, but it cannot fill all gaps.